Complications and outcomes of routine endoscopy in the very elderly - Miyanaga, Ryoichi; Hosoe, Naoki; Naganuma, Makoto; Hirata, Kenro; Fukuhara, Seiichiro; Nakazato, Yoshihiro; Ojiro, Keisuke; Iwasaki, Eisuke; Yahagi, Naohisa; Ogata, Haruhiko; Kanai, Takanori (Endoscopy International Open, 2018)
Background and study aims In Japan, the elderly population has been increasing annually. The number of elderly patients for whom esophagogastroduodenoscopy (EGD) and colonoscopy (CS) is indicated also has been rising. The aim of this study was to evaluate the safety and efficacy of routine endoscopy in a cohort of octogenarians aged 85 years and older – defined by the World Health Organization as the very elderly.Patients and methods A total of 5,586 patients underwent EGDs, and 2,484 patients underwent CSs performed at the Keio University Hospital from January to September 2014. One hundred eighty-five EGDs and 70 of the CS were performed in the very elderly. Six hundred nine EGDs and 262 CS were performed on younger patients (aged forties). Statistical analysis was performed by univariate and multivariate analyses. Results On univariate analysis, the rate of adverse events (AEs) in the very elderly was significantly higher compared to the younger group (6.3 % vs. 1.1 %; P < 0.01). Moreover, the very elderly cohort received substantial therapeutic intervention as compared to the younger (16.9 % vs. 6.9 %; P < 0.01). On multivariate analysis, independent risk factors of AEs included: very elderly patients (odds ratio (OR) 3.30, 95 % confidence interval (CI) 1.05 – 10.35), inpatients (OR 3.22, 95 % CI 1.34 – 7.74), and use of pethidine hydrochloride prescription (OR 3.44, 95 % CI 1.51 – 7.81). Conclusions Routine endoscopy in the very elderly incurs a significant risk of AEs, particularly when combined with pethidine hydrochloride prescription.